Pharmaceutical lobbying in Brazil: a missing topic in the public health research agenda - Francisco José Roma Paumgartten
ABSTRACT In the US, where registration of lobbyists is mandatory, the pharmaceutical industry and private health-care providers spend huge amounts of money seeking to influence health policies and government decisions. In Brazil, where lobbying lacks transparency, there is virtually no data on drug industry expenditure to persuade legislators and government officials of their viewpoints and to influence decision-making according to commercial interests. Since 1990, however, the Associação da Indústria Farmacêutica de Pesquisa (Interfarma - Pharmaceutical Research Industry Association), Brazilian counterpart of the Pharmaceutical Research and Manufacturers of America (PhRMA), main lobbying organization of the US pharmaceutical industry, has played a major role in the advocacy of interests of major drug companies. The main goals of Interfarma lobbying activities are: shortening the average time taken by the Brazilian regulatory agency (ANVISA) to approve marketing authorization for a new drug; making the criteria for incorporation of new drugs into SUS (Brazilian Unified Health System) more flexible and speeding up technology incorporation; changing the Country's ethical clearance system and the ethical requirements for clinical trials to meet the need of the innovative drug industry, and establishing a National Policy for Rare Diseases that allows a prompt incorporation of orphan drugs into SUS. Although lobbying affects community health and well-being, this topic is not in the public health research agenda. The impacts of pharmaceutical lobbying on health policies and health-care costs are of great importance for SUS and deserve to be investigated.